Low Risk for Arrhythmic Events in Asymptomatic Patients With Drug-Induced Type 1 ECG: Do Patients With Drug-Induced Brugada Type ECG Have Poor Prognosis? (Con) - Sakurada, Harumizu; Ueda-Tatsumoto, Akiko; Nishizaki, Mitsuhiro; Hiraoka, Masayasu; Yamawake, Noriyoshi (Circulation Journal, 2010)
The type 1 ST-segment elevation is diagnostic for Brugada syndrome (BS) and its presence may sometimes be associated with a high risk of arrhythmic events. The type 1 ECG is also known to be unmasked by administration of sodium-channel blockers in equivocal or suspected cases of BS, and the drug-challenge test is frequently used in the diagnostic approach. In large cohort studies the spontaneous appearance of the type 1 ECG with symptoms of aborted sudden death or unexplained syncope are indicative of a poor prognosis for patients with BS compared with not having clinical symptoms. Therefore, the spontaneous type 1 ECG appears to represent an important predictive sign for cardiac events. It is unknown, however, whether or not the drug-induced type 1 ECG is as useful as the spontaneous type 1 for predicting cardiac events in asymptomatic subjects showing non-type 1 ECG. Review of the literature for large cohort studies indicates that there is a low incidence of arrhythmic events in asymptomatic patients with either the spontaneous or drug-induced type 1 ECG compared with symptomatic subjects, and the drug-induced type1 ECG in asymptomatic patients does not add to an increase in arrhythmic risk. Therefore, drug testing to unmask the type 1 ECG in asymptomatic patients with a non-type 1 BS ECG does not have an additional value for risk stratification of cardiac events, although it might be useful in symptomatic patients showing only the non-type 1 ECG. (Circ J 2010; 74: 2464-2473)